The Self-development of Personality on the Psychognostic Stage of Development - Kolisnyk, Oleksij (Psychological Prospects Journal, 2016)
Man’s consciousness reliance on the conventional signs, in which the communal and own experience of interaction with typical circumstances has been encoded by means of concepts, perfectly mediates a specific interaction and creates conditions to control the generated actions and reflexive reconstruction of this circumstances. Reflection as an ideal capacity of the individual to consider speculatively information, opens for him the opportunity of creative transcedence beyond itself and circumstances towards the actualization of resources for more effective interaction with the world. The voluntary productive transformation of the system of personality concepts serves as a mental mechanism of personality self-development.Key words: sign, sign system, concept, worldview, mediation, aim, dysfunctional and inadequate concepts, frustration, reflection, self-development of personality.